2016
DOI: 10.1089/acm.2014.0400
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Acupuncture for the Treatment of Functional Dyspepsia: Meta-Analysis

Abstract: Acupuncture appears to be efficacious in relieving FD symptoms and improving quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…Acupuncture has long been used in China to treat FD, and it has been used in some Western countries as an optional treatment for gastrointestinal diseases due to its high efficacy and safety [4][5][6]. Studies have shown that RN12, ST36, ST37, PC6, ST25, and BL21 are principal acupoints for the treatment of gastrointestinal diseases [7].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture has long been used in China to treat FD, and it has been used in some Western countries as an optional treatment for gastrointestinal diseases due to its high efficacy and safety [4][5][6]. Studies have shown that RN12, ST36, ST37, PC6, ST25, and BL21 are principal acupoints for the treatment of gastrointestinal diseases [7].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several articles on the meta-analysis of the acupuncture treatment for FD. One article reported that there was no significant difference between domperidone and manual acupuncture in improving symptom scores (RR: (Zhou WM et al, 2016). In addition, we also performed frequency analysis and cluster analysis on 60 acupuncture prescriptions of 31 RCTs, the results showed that ST35, P6, CV12, ST25, LR3, BL21,, BL2, CV6, LR14 and CV10 were the most frequently used acupoints, and ST36, P6, CV12;ST25, BL20, BL21;LR14, LR2, BL18, LR3;SP9,ST44 were the main acupoints groups treating for FD.…”
Section: Frequency Analysis Of Acupointmentioning
confidence: 99%
“…In recent years, several systematic reviews [19][20][21][22] have shown that different acupuncture therapies effectively improve functional dyspepsia, even better than conventional drugs. So far, many types of acupuncture therapies have been developed, including manual acupuncture [23], warm acupuncture [24], electroacupuncture [25], moxibustion [26], acupoint catgut embedding [27], and acupoint application [28].…”
Section: Introductionmentioning
confidence: 99%
“…So far, many types of acupuncture therapies have been developed, including manual acupuncture [23], warm acupuncture [24], electroacupuncture [25], moxibustion [26], acupoint catgut embedding [27], and acupoint application [28]. Previous systematic reviews [19][20][21][22] have only evaluated the efficacy of different acupuncture therapies as a whole in comparison with conventional drugs. In 2017, Ho et al conducted a systematic review and network metaanalysis on acupuncture and other related therapies for functional dyspepsia.…”
Section: Introductionmentioning
confidence: 99%